2015
DOI: 10.1136/bmjopen-2015-007633
|View full text |Cite
|
Sign up to set email alerts
|

Screening for the metabolic side effects of antipsychotic medication: findings of a 6-year quality improvement programme in the UK

Abstract: ObjectivesTo increase the frequency and quality of screening for the metabolic syndrome in people prescribed continuing antipsychotic medication.DesignAn audit-based, quality improvement programme (QIP) with customised feedback to participating mental health services after each audit, including benchmarked data on their relative and absolute performance against an evidence-based practice standard and the provision of bespoke change interventions.SettingAdult, assertive outreach, community psychiatric services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 23 publications
0
36
1
Order By: Relevance
“…The proportion of patients assessed for metabolic side effects was relatively low compared with community-based patients with schizophrenia,25 26 perhaps partly due to the additional challenges associated with phlebotomy in people with ID.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients assessed for metabolic side effects was relatively low compared with community-based patients with schizophrenia,25 26 perhaps partly due to the additional challenges associated with phlebotomy in people with ID.…”
Section: Discussionmentioning
confidence: 99%
“…16 Thus, the potential for psychotropic drugs to cause or to exacerbate metabolic syndrome in patients is not restricted to at-risk patients (eg, drug naive, first episode disease, and nonobese or young patients). 11 Because clinicians have been found to have a poor adherence to guidelines for metabolic monitoring worldwide, [27][28][29] there is a need for programs to help educate providers and to facilitate monitoring of these cardiometabolic risk factors. Beside, a poor quality of management of potential physical health problems in psychiatric patients has also been recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, clinical guidelines for metabolic screening upon initiation or continuation of SGAs put forth that blood pressure, body mass index (BMI), blood glucose and lipids should be checked at least every six months. [131][132][133] This has been a highly positive and well-received step towards better considering the physical health outcomes in people with SMI. However, decades of research in the general population have shown that preventing conditions such as obesity and metabolic syndrome from ever arising is considerably more efficient than attempting to reverse their long-term consequences.…”
Section: Panel 2: Why Wait For Weight? Tipping the Scales Towards Prementioning
confidence: 99%